Planar super-oscillatory lens for sub-diffraction optical needles at violet wavelengths - Yuan, Guanghui (2015)
Planar optical lenses are fundamental elements of miniaturized photonic devices. However, conventional planar optical lenses are constrained by the diffraction limit in the optical far-field due to the band-limited wavevectors supported by free-space and loss of high-spatial-frequency evanescent components. As inspired by Einstein's radiation ‘needle stick’, electromagnetic energy can be delivered into an arbitrarily small solid angle. Such sub-diffraction optical needles have been numerically investigated using diffractive optical elements (DOEs) together with specially polarized optical beams, but experimental demonstration is extremely difficult due to the bulky size of DOEs and the required alignment precision. Planar super-oscillatory lenses (SOLs) were proposed to overcome these constraints and demonstrated that sub-diffraction focal spots can actually be formed without any evanescent waves, making far-field, label-free super-resolution imaging possible. Here we extend the super-oscillation concept into the vectorial-field regime to work with circularly polarized light, and experimentally demonstrate, for the first time, a circularly polarized optical needle with sub-diffraction transverse spot size (0.45λ) and axial long depth of focus (DOF) of 15λ using a planar SOL at a violet wavelength of 405 nm. This sub-diffraction circularly polarized optical needle has potential applications in circular dichroism spectroscopy, super-resolution imaging, high-density optical storage, heat-assisted magnetic recording, nano-manufacturing and nano-metrology.